Ответы 1

  • tg(\frac{\pi }{4}-arcctg2)=\frac{tg\frac{\pi}{4}-tg(arcctg2)}{1+tg\frac{\pi}{4}\cdot tg(arcctg2)}= \frac{1-tg(arctg\frac{1}{2})}{1+tg(arctg\frac{1}{2})}=\frac{1-\frac{1}{2}}{1+\frac{1}{2}}=\frac{1}{3}\\\\\\tg(arcctgx)=tg(arctg\frac{1}{x})=\frac{1}{x}\; ,\; \; x\in ( 0,\pi )
    • Автор:

      pecanktnm
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years